DIGITAL MARKETING “GOOGLE BISNISKU” PADA UMKM UNTUK MENINGKATKAN PEMASARAN DAN PENJUALAN PRODUK PADA MASA PANDEMI COVID-19 - Ni Komang Sri Yuliastini; Ni Luh Putu Cahayani; Ni Putu Yuniarika Parwati; Luh De Liska (LPPM Universitas PGRI Mahadewa Indonesia, 2021)
UMKM are one of the strengths of the national economy. During the Covid-19 pandemic, UMKM are the sector most vulnerable to being affected, especially in terms of product marketing and sales. MSME Pande Urip Wesi (PAUWE) is a business engaged in iron equipment. This service activity aims to help the problems faced by Pande Urip Wesi. The solution offered in this activity is to implement digital marketing using the Google My Business application. This application can help UMKM actors so that their business can be found by potential customers on Google searches and maps. The method used in this activity consists of forming an activity team, conducting analysis, implementing activities and evaluating. The result of this service activity is the Google My Business application as a tool for online marketing and sales as well as providing training to business owners to have the ability to operate the Google My Business application.